Incidence and Risk Factors of Urinary Tract Infection in Patients with Diabetes Mellitus Using Dapagliflozin in Benghazi, Libya - Asma Buzgeia,; Nuri Badi,; Ghadah Alagouri,; Nazik Hamad,; Bushray Sulayman,; Fatima Alzahra Tarhouni, (AlQalam Journal of Medical and Applied Sciences, 2025)
Diabetes mellitus (DM) is the most prevalent endocrine disorder, impacting over 100 million individuals globally. Dapagliflozin has been extensively examined as an alternative therapy for type 2 diabetes, alongside metformin, sulfonylureas, sitagliptin, glucagon-like peptide-1 receptor agonists, and insulin. The objective of this study is to evaluate the association between the use of Forxiga (dapagliflozin) and the incidence of urinary tract infections among patients with diabetes. A cross-sectional study was conducted using 14 self-assessment questionnaires at the National Center for Diabetes Diagnosis and the National Cardiac Center in Benghazi, Libya. The research took place over six months, from April to October 2025. Upon examining the status of urinary tract infections (UTIs), the data show that the overwhelming majority (86.7%) of participants were not infected. Regarding the period of drug use, most participants had used Forxiga for durations ranging between one month and one year. Overall, the statistical results show no significant relationship between the incidence of UTI and the period of drug use or gender. However, they revealed a strong association between the prevalence of infection and age. This descriptive analytical study focused on evaluating the efficacy of dapagliflozin (Forxiga) in adult patients with diabetes, with particular attention to its most common side effect—urinary tract infection (UTI)—as well as treatment adherence duration. The study included a total sample of 100 participants: a main group of 70 patients using dapagliflozin and a control group of 30 patients using other glucose-lowering medications. This study affirms the high efficacy of dapagliflozin in lowering blood glucose levels. Importantly, while confirming an increased incidence of UTI associated with dapagliflozin compared to standard treatments, the study also indicates that these infections are predominantly mild to moderate in severity, supporting the drug’s overall favorable risk–benefit profile.